Video Edukasi Bank Sampah Untuk Membangun Sociopreneurship Karang Taruna Desa Pamijahan Bogor - Mahdalena, Vina; Riyantini, Rini; Sutowo, Irpan Ripa’i (Universitas Mataram, 2024)
Data for 2022, Bogor district waste reaches 2,800 tons per day. The Waste Bank is one of the solutions to environmental problems that occur in Bogor Regency, besides that the Waste Bank is a forum for the community to remain empowered to generate profits from the waste sorting process. This concept is in line with sociopreneurship (social entrepreneurship) which focuses primarily on social missions and goals to the commercial side. Departing from social goals, youth Indonesians must be empowered to achieve big social missions. So, the subject of community service activities carried out in Pamijahan Village is youth development who can be involved in village programs. Video is one of the closest and easily accessible media for generation Z (17-26 years). Therefore, we designed communication media by making video media as a source of information for youth development in Pamijahan Village, Bogor Regency. Based on the results of the pre-test and post-test, it showed that there was an increase in knowledge of them. Changing cognition is expected to build awareness of the importance of the Waste Bank and bring out the spirit of sociopreneurship (social entrepreneurship) in youth development for a sustainable village program.